The legality of terminating pregnancy from the Malaysian and Islamic law perspectives - Jahn Kassim, Puteri Nemie; Mohamad Hussain, Mazlena (Jordan Society for Islamic Medical Sciences & Federation of Islamic Medical Associations, 2019)
Terminating Pregnancy or more commonly known as Abortion is one of the most controversial areas in medical law and ethics. The ‘legality of terminating pregnancy’ debate that has taken place is immensely wide-ranging, embracing numerous concepts, such as the beginning of human life, sanctity of life and the autonomy of the woman to choose on whether to reproduce and determine the fate of her unborn child. Judicial interventions in this area have taken into account not only the legal and ethical dilemmas, but religious viewpoints as well. Although terminating pregnancy has remained unlawful in Malaysia, there are several exceptions that have made it lawful. The Malaysian Penal Code (Revised 1997) (Act 574) through the exception under provision 312 has made terminating pregnancy lawful if the “continuance of the pregnancy would involve risk to the life of the pregnant woman, or injury to the mental or physical health”. Religious viewpoints on the issue of terminating pregnancy have also been predominant amongst the Malaysian society. Islam regards life, including that of a fetus, as sacred. Although there are no direct verses in the Holy Qur’an that prohibit termination of pregnancy but there are many verses that prohibit taking away life without legitimate reasons. Thus, terminating pregnancy under Islamic law can be lawful if done for legitimate reasons. Nevertheless, there is diversity of opinions amongst the Muslim scholars on whether terminating pregnancy can be conducted within a stipulated time. This paper seeks to discuss the legality of terminating pregnancy from the Malaysian and Islamic Law perspectives.